Pengaruh Pengembangan Karir dan Pelatihan Kerja terhadap Motivasi Kerja Pegawai Rumah Sakit Cut Nyak Dhien - Riny Chandra; Syardiansah Syardiansah (Universitas Negeri Medan, 2021)
This study aims to determine the effect of career development and job training on work motivation of the employees of the Langsa City Cut Nyak Dhien Hospital. The population in this study were all employees totaling 34 people. The sampling technique was non-probability sampling with saturated sampling, so that all populations were sampled in this study. The results showed that the resulting liner regression model was Y = 5.597 - 0.192X1 - 0.054X2. Career development variables have a negative effect on employee work motivation by -0.192 and job training variables have a negative effect on employee motivation by -0.054, so that career development and job training do not need to be given at this time because of 5.597 values which have very good meanings the work motivation of the employees of the Langsa City Cut Nyak Dhien Hospital at this time. Partially career development and job training have an insignificant effect on employee motivation. And simultaneously career development and job training have an insignificant effect on employee motivation. Based on the value of the coefficient of determination, only 4% of career development and job training variables can explain the variables of work motivation for the employees of the Langsa City Cut Nyak Dhien Hospital.